2014
DOI: 10.1371/journal.pone.0093600
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Learning with SVM for Multimodal Classification of Prostatic Adenocarcinoma

Abstract: Robust detection of prostatic cancer is a challenge due to the multitude of variants and their representation in MR images. We propose a pattern recognition system with an incremental learning ensemble algorithm using support vector machines (SVM) tackling this problem employing multimodal MR images and a texture-based information strategy. The proposed system integrates anatomic, texture, and functional features. The data set was preprocessed using B-Spline interpolation, bias field correction and intensity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 64 publications
(98 reference statements)
0
17
0
Order By: Relevance
“…The combination of anatomic (T2W) images and functional techniques has been shown to increase the accuracy of MR imaging for diagnosis of PCa. Table 1 compares the performance of the major published prostate CADx systems [13, 14, 1618, 22, 26, 27, 36, 37, 39, 51, 52, 5457, 62, 122, 129, 140151]. Chan et al.…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of anatomic (T2W) images and functional techniques has been shown to increase the accuracy of MR imaging for diagnosis of PCa. Table 1 compares the performance of the major published prostate CADx systems [13, 14, 1618, 22, 26, 27, 36, 37, 39, 51, 52, 5457, 62, 122, 129, 140151]. Chan et al.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…For cases in which radiologists are less confident, they can get higher performance by using the computer output. A recent study showed a pattern recognition system enables radiologists to have a lower variability in diagnosis, decreases false negative rates, and reduces the time to recognize and delineate structures in the prostate [16]. The benefit of CADx also includes guiding biopsy using cancer location information from MRI [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several CAD systems adopting a multiparametric approach have been developed. T2W MRI was combined with DCE MRI, 8,9 diffusion-weighted imaging (DWI), 10 or MR spectroscopy. 11,12 Some incorporated T2W MRI, DCE MRI, and DWI together.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] Intensity 8,10,[13][14][15][16]19 and texture [9][10][11]16,18 features were commonly used to characterize suspicious lesions. Texture features included first-order statistics, 9,16 co-occurrence matrix, 10,16 gradient operators, 16,18 local binary pattern, 18 local phase quantization, 9 and wavelet transform. 11 In addition, graph embedding, 12,21 random walk, 17 locally linear embedding, 15 and principal component analysis 11 were used to reduce data dimension and/or to improve data representation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation